2017
DOI: 10.1038/s41598-017-17331-z
|View full text |Cite
|
Sign up to set email alerts
|

MiR-211 is essential for adult cone photoreceptor maintenance and visual function

Abstract: MicroRNAs (miRNAs) are key post-transcriptional regulators of gene expression that play an important role in the control of fundamental biological processes in both physiological and pathological conditions. Their function in retinal cells is just beginning to be elucidated, and a few have been found to play a role in photoreceptor maintenance and function. MiR-211 is one of the most abundant miRNAs in the developing and adult eye. However, its role in controlling vertebrate visual system development, maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…This pathway is likely to play a physiologically relevant role in the RPE since mice lacking miR‐211 show impaired lysosomal biogenesis and an age‐dependent accumulation of phagolysosomes containing poorly processed POS, accompanied by compromised vision. Finally, we show that pharmacological inhibition of Ezrin leads to therapeutic rescue of retinal degeneration in miR‐211 knockout (−/−) mice (Barbato et al , ). Thus, the identification of the mechanisms controlling lysosomal biogenesis in the RPE might be exploited for new therapeutic possibilities for the treatment of retinal degeneration associated with lysosomal dysfunction.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This pathway is likely to play a physiologically relevant role in the RPE since mice lacking miR‐211 show impaired lysosomal biogenesis and an age‐dependent accumulation of phagolysosomes containing poorly processed POS, accompanied by compromised vision. Finally, we show that pharmacological inhibition of Ezrin leads to therapeutic rescue of retinal degeneration in miR‐211 knockout (−/−) mice (Barbato et al , ). Thus, the identification of the mechanisms controlling lysosomal biogenesis in the RPE might be exploited for new therapeutic possibilities for the treatment of retinal degeneration associated with lysosomal dysfunction.…”
Section: Introductionmentioning
confidence: 71%
“…However, the functional significance of their light‐dependent expression pattern in the RPE/retina remains largely unknown. Our previous work showed that miR‐211 plays a key role in cone PR function and survival through the control of RPE/PR cell metabolism (Barbato et al , ). However, the link between the miR‐211 molecular network and cellular metabolism and its specific influence on explicit target genes responsible for the ocular phenotype is still undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Scotopic and photopic electrophysiological recordings were performed as described (Barbato et al, 2017). A National Instruments amplifier with a xenon Ganzfeld stimulator (CSO, Costruzione Strumenti Oftalmici, Florence, Italy) was used to record MPS-IIIA mice.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…In this study, we also found that chi-miR-211 was highly expressed in cashmere goat skin in summer. MiR-211 is essential for adult cone photoreceptor maintenance [26]. These results suggested that some cells in the skin could have the potential of photosensitive, which could maintain the specific rhythm of the peripheral organs based on the environment factor (photoperiod).…”
Section: Discussionmentioning
confidence: 89%